Transient Receptor Potential Signaling Pathways Influence the Hyperalgesia in a Rat Model of Mechanical Lumbar Disc Herniation. Issue 3 (2nd October 2015) - Zhao, Ling-Rui; Xing, Run-Lin; Zhang, Li; Xu, Bo; Li, Xiao-Chen; Wang, Pei-Min
Abstract: Lumbar disc herniation [LDH] is a common chronic orthopedic disease which often leads to severe pain and distress. Mechanical pressure and local chemical disturbance are the main factors that cause the pain in LDH. In recent years, many studies have confirmed that transient receptor potential channels [TRPs] are the main cell signaling pathways that regulate the mechanism of pain sensitivity. This study intends to explore the relationship between TRPs and the chronic pain sensitivity of LDH. Thirty SD rats were randomly divided into the normal group and the LDH group. The LDH group used autologous nucleus pulposus entrapment to manufacture LDH model and 2 weeks later, dorsal root ganglion tissue is dissected to detect the change of pain threshold, protein and gene expressions of TRPA1, TRPV4 and TRPM8. The results showed that in the LDH group, both cold and mechanical pain threshold were lower than the normal group, the protein and gene expressions of TRPA1 and TRPM8 were higher than that of the normal group, while the protein and gene expressions of TRPV4 were lower than the normal group. This study confirmed that the pain sensitivity mechanism of LDH may be probably related to the regulation of TRPs.